2014
DOI: 10.1093/ejcts/ezu456
|View full text |Cite|
|
Sign up to set email alerts
|

Morphological and functional consequences of transradial coronary angiography on the radial artery: implications for its use as a bypass conduit†

Abstract: RA-CA produces extensive damage to the RA. The lesions tend to heal with time but incomplete recovery of endothelial integrity and function is still present more than 30 days after the procedure. After RA-CA, the cannulated RA should not be used for CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…A recent study by Gaudino et al 18 has provided further evidence of endothelial damage following TR procedures. This group examined 50 patients who underwent TR coronary angiography (RA-CA) before RA harvesting for CABG, and split the patients into 3 groups depending on the time interval between the RA-CA procedure and the evaluation of their RA (≤24 hours, >24 hours to <7 days, and ≥7 days).…”
Section: Does Previous Transradial Catheterization Preclude Use Of Thmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent study by Gaudino et al 18 has provided further evidence of endothelial damage following TR procedures. This group examined 50 patients who underwent TR coronary angiography (RA-CA) before RA harvesting for CABG, and split the patients into 3 groups depending on the time interval between the RA-CA procedure and the evaluation of their RA (≤24 hours, >24 hours to <7 days, and ≥7 days).…”
Section: Does Previous Transradial Catheterization Preclude Use Of Thmentioning
confidence: 92%
“…15,17 In addition to its role in CABG, the RA also is being used with increasing frequency as the access point for coronary angiography and percutaneous coronary interventions in the diagnosis and management of coronary artery disease, respectively. 18 Although, traditionally, the femoral artery has been the preferred route, recent studies have demonstrated that the transradial (TR) approach holds numerous advantages over the transfemoral approach, including decreased bleeding site complications, reduced cost, and a reduction in mortality. 19,20 Moreover, patients prefer the TR approach because of its shorter hospital stay, increased comfort, and better physical functioning postprocedure.…”
Section: Does Previous Transradial Catheterization Preclude Use Of Thmentioning
confidence: 99%
“…Endothelial dysfunction of RA possibly results from endothelial denudation injury as induced in animal models [15]. Complete or incomplete recovery of endothelial dysfunction is expected from as early as 24 h [16] up to 14 months after procedure [6,9,12,17] although persistent impairment of RA function has also been reported [7,10,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, long-term ultrasound examination could find out the incidence of persistent injury or further recovery of vasodilatory function, if any. However, long-term effects of sheath injury are controversial and dependent on the time of assessment after procedure, as discussed previously [6].…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation